Impact of nanoscale silicon dioxide coating of stainless-steel surfaces on Listeria monocytogenes - Hillig, Nadja; Schumann-Muck, Felicitas; Hamedy, Ahmad; Braun, Peggy G; Koethe, Martin (Folia microbiologica, 2024)
High resistance to environmental factors as well as the ability to form biofilms allow Listeria monocytogenes to persist for a long time in difficult-to-reach places in food-producing plants. L. monocytogenes enters final products from contaminated surfaces in different areas of plants and poses a health risk to consumer. Modified surfaces are already used in the food industry to prevent cross-contamination. In this study, stainless-steel surfaces were coated with nanoscale silicon dioxide and the effects on attachment, bacterial growth and detachment of L. monocytogenes were evaluated. Attachment was considered for three different ways of application to simulate different scenarios of contamination. Bacterial growth of L. monocytogenes on the surface was recorded over a period of up to 8 h. Detachment was tested after cleaning inoculated stainless-steel surfaces with heated distilled water or detergent. Coating stainless-steel surfaces with nanoscale silica tends to reduce adherence and increased detachment and does not influence the bacterial growth of L. monocytogenes. Further modifications of the coating are necessary for a targeted use in the reduction of L. monocytogenes in food-processing plants.
Keywords: Food Microbiology; potravinářská mikrobiologie; kontaminace potravin; Listeria monocytogenes; biofilmy; počet mikrobiálních kolonií; Stainless Steel; bakteriální adheze; Biofilms; Bacterial Adhesion; nerezavějící ocel; Colony Count, Microbial; Food Contamination